Enhancing Apple Production and Market Linkages in Mountain Regions: Challenges and Opportunities - Mahat, Dhana Krishna (The Third Pole: Journal of Geography Education, 2024)
This article reviews the current state of apple production in mountain regions, emphasizing the challenges faced by farmers and the opportunities to enhance market linkages. Based on case studies at the municipal level of Jumla district and existing literature, the study identifies key factors influencing production and market access. It proposes strategies for improvement, and highlights the importance of sustainable practices for the development of apple production, market linkage and sustainable agriculture in rural areas. Spatial locations of the study area are relatively safe from different kinds of risks and viable for apple farming at commercial level. Further, the natural, cultural and ecological conditions of these specific locations are suitable to promote organic apple farming with agro-based enterprises development activities. Study clearly evinces that capacity development of apple cultivation farmers needs to enhance for increasing apple production and marketing in wright for livelihood improvement and ecological stability in the mountain region. It is suggested that municipal annual plan needs to prioritize apple production and make link mechanism development for the rapid economic development (growth), social change and environmental balance.